Involuntary Hospitalization of Patients With Mental Disorders: Knowledge of Health Professionals - Arena Ventura, Carla Aparecida; Fernandes Moll, Marciana; Correia, Rubens; Oyan de Moraes, Viviana Carolina [UNESP]; Duarte Silva, Lucas; Costa Mendes, Isabel Amélia (Elsevier, 2016)
A descriptive and exploratory study with a qualitative approach was undertaken to describe the knowledge of health professionals at a psychiatric hospital about involuntary hospitalization. Health professionals from the admission ward of a psychiatric hospital located in an inner city of the state of São Paulo, Brazil, participated in the study. Data were collected through semistructured interviews with sixteen health professionals and the analysis was based on thematic analysis. The professionals' lack of knowledge about involuntary hospitalizations was evidenced, including unfamiliarity with the modalities of psychiatric hospitalization, confusion to understand involuntary and compulsory hospitalization as well as the role of the public prosecutor in these cases. In that sense, the study participants' lack of knowledge and, on the other hand, the inertia of the public prosecutor's office can hamper the full enjoyment of rights by persons with mental disorders. In this scenario, psychiatric health professionals should know and understand the legislation as well their responsibility according to it, combining political with theoretical–technical knowledge.